"Conquistadors" in Central Africa : nature, hunting and colonial wars in the Congo Free State (1880s - 1900s) - (:unkn) unknown (My University, 2018)
Central Africa has been characterized by a very long thirty years war from the 1880s to the 1900s as the Congo Free State, the private property of the King of the Belgians Leopold II, was built up in the region. This thesis aims at analysing armed violence and conflicts occurring in the Congo area at the end of the 19th Century and studying war experiences of European soldiers involved in the colonial conquest – also named “conquistadors”. This research is based on a various sources such as private archives (letters, memoirs, notebooks), state archives (commission of inquiry) and iconographic material (drawings, photographs), embracing a large social history of those soldiers from their departure to the Congo to their return in Europe. The analysis of their representations and practices during the colonial conquest period reveals one key element, i.e. the importance of their relationship to nature and wildlife. As fierce hunters they define the natural world and populations as many examples of savagery that need to be domesticated and controlled. Thus this research showcases the strong links established by those men between hunting and war of conquest. Those European soldiers think of themselves as powerful chiefs, well armed and helped by a mighty colonial army, the Force Publique. They have developed hunting gestures and practices that helped them to submit indigenous peoples and impose forced labour. This thesis especially argues that such hunting model is very significant in the rubber wars that were led by the Congo Free State and private companies; it also shows the importance of trophies in colonial war experiences. The links between hunting and war are finally well-exemplified back in Europe when those soldiers displayed African items and animal trophies.
Keywords: African Research